Totally intracorporeal robot‐assisted radical cystectomy: optimizing total outcomes. (5th March 2014) - Collins, Justin W.; Wiklund, N. Peter
<x xml:space="preserve">Abstract</x> We performed a systematic literature review to assess the current status of a totally intracorporeal robot‐assisted radical cystectomy (RARC) approach. The current 'gold standard' for radical cystectomy remains open radical cystectomy. RARC has lagged behind robot‐assisted prostatectomy in terms of adoption and perceived patient benefit, but there are indications that this is now changing. There have been several recently published large series of RARC, both with extracorporeal and with intracorporeal urinary diversions. The present review focuses on the totally intracorporeal approach. Radical cystectomy is complex surgery with several important outcome measures, including oncological and functional outcomes, complication rates, patient recovery and cost implications. We aim to answer the question of whether there are advantages to a totally intracorporeal robotic approach or whether we are simply making an already complex procedure more challenging with an associated increase in complication rates. We review the current status of both oncological and functional outcomes of totally intracorporeal RARC compared with standard RARC with extraperitoneal urinary diversion and with open radical cystectomy, and assess the associated short‐ and long‐term complication rates. We also review aspects in training and research that have affected the uptake of RARC. Additionally we evaluate how current technology is contributing to the future development of this surgical technique.